Pengembangan Media Pembelajaran Berbasis Role Playing Game (RPG) Untuk Siswa Kelas X SMK Negeri 3 Yogyakarta - Swadyaya, Putu Yana; Arifin, Fatchul (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
The purpose of this study is to develop a game like learning media program about resistor's color code reading and simple resistor circuits made in RPG Maker MV game engine for grade X vocational school student. The developed learning media includes: learning media program, student workbook, and a complementary module book. The method of research and development is used in this study. Descriptive analysis was used on the feasibility analysis of learning media. Result of experts and users test validation stated that the developed learning media is in the feasible category based on all validated and tested aspects. First educational expert's assessment shows feasibility level of 93.04% (Very Feasible). Second educational expert's assessment shows feasibility level of 72.17% (Feasible). First media expert's assessment shows feasibility level of 86.65% (Very Feasible). Second media expert's assessment shows feasibility level of 89.29% (Very Feasible). User trial assessment shows feasibility level of 78.52% (Feasible)